Evaluasi Kualitas Layanan SILAKAN Banyuwangi menggunakan Metode E-GovQual dan Importance Performance Analysis (IPA) - Fadliansyah, Alfian Nur; Juwita, Oktalia; Arifin, Fajrin Nurman (Politeknik Indonusa Surakarta, 2023)
The SILAKAN application stands for the Banyuwangi Regency Personnel Service System developed by BKPP Banyuwangi Regency. Obstacles when using this SILAKAN service such as, services are still limited to using mobile applications, the speed when loading services is still slow, slow responses when there are problems so that users have to come to the office, and downloading documents is quite slow. This research was conducted to evaluate the quality of SILAKAN Banyuwangi services using the e-GovQual and IPA methods. Evaluation of service quality based on users, namely all ASNs in Banyuwangi Regency. The results of the study showed that the total performance score on all e-GovQual variables above Likert score 3 was 3.36 and the total interest assessment score was 3.42, resulting in a gap between performance and interests of -0.06. A negative value gap indicates that service performance still does not meet user interests. Based on the analysis of conformity between performance and interests has a conformity value of 98.23%. There are 4 attributes that fall into quadrant 1 which means getting the top priority for improvement, namely, this e-Government site successfully performs services based on the first request (RB3), this e- Government site is available and can be accessed whenever you need it (RB2), the data provided by users on this e-Government site is archived safely (TR3), employees give prompt replies to user questions (CS2).